2021
DOI: 10.1186/s12891-021-04366-7
|View full text |Cite
|
Sign up to set email alerts
|

Limited predictive value of illness perceptions for short-term poor recovery in musculoskeletal pain. A multi-center longitudinal study

Abstract: Background Musculoskeletal pain (MSP) is recognized worldwide as a major cause of increased years lived with disability. In addition to known generic prognostic factors, illness perceptions (IPs) may have predictive value for poor recovery in MSP. We were interested in the added predictive value of baseline IPs, over and above the known generic prognostic factors, on clinical recovery from MSP. Also, it is hypothesized there may be overlap between IPs and domains covered by the Four-Dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…Two studies confirm our results: A study by de Raaij et al. [ 41 ] assessing the effect of physiotherapy on 251 patients with musculoskeletal pain found limited predictive value of baseline IP on pain and functional level and another similar study by Hallegraeff et al. [ 42 ], on 204 patients with acute nonspecific low back pain found similar results.…”
Section: Discussionsupporting
confidence: 88%
“…Two studies confirm our results: A study by de Raaij et al. [ 41 ] assessing the effect of physiotherapy on 251 patients with musculoskeletal pain found limited predictive value of baseline IP on pain and functional level and another similar study by Hallegraeff et al. [ 42 ], on 204 patients with acute nonspecific low back pain found similar results.…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, there are no studies on predictive factors in accordance with the ones presented here regarding a patient population with chronic, severe pain who has completed a similar one-to-one, physiotherapist-led rehabilitation program. Various patient-populations with various severeness of symptoms have been studied, various content of rehabilitation programs have been used, and the studies have been performed in various health care settings in specialized and in primary care [20,23,[40][41][42][43][44][45][46][47][48][49][50][51]. Moreover, the previous literature shows somewhat conficting results of that; no strong predictive baseline variables exist to predict successful outcome [20-23, 42, 46, 47], and worse baseline status can be associated with improved outcome after rehabilitation [23,40,42,[46][47][48], but also that poor pretreatment physical and psychological functioning at the baseline can have a negative prognosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the previous literature shows somewhat conficting results of that; no strong predictive baseline variables exist to predict successful outcome [20-23, 42, 46, 47], and worse baseline status can be associated with improved outcome after rehabilitation [23,40,42,[46][47][48], but also that poor pretreatment physical and psychological functioning at the baseline can have a negative prognosis [20]. Also, in previous studies, various outcomes and predictive baseline variables are used [20,23,[40][41][42][43][44][45][46][47][48][49][50][51]. All these factors reveal the complexity of the research feld and make comparisons between studies, the present one included, challenging.…”
Section: Discussionmentioning
confidence: 99%
“… 30 The same trend was seen for musculoskeletal pain, where IPQ did not add substantially to the prediction of recovery. 10 Similarly, a secondary analysis of a randomised controlled trial published in 2018 showed that high levels of fear-avoidance beliefs measured by the Fear-Avoidance Beliefs Questionnaire in patients with LBP were only weakly associated with worse outcomes in LBP and disability at 12 months, yet the association was much stronger for sick leave. 31 However, both the IPQ and Fear-Avoidance Beliefs Questionnaire cover more domains than the BBQ and the results are therefore not directly comparable.…”
Section: Discussionmentioning
confidence: 99%
“… 9 However, a recent longitudinal study from 2021 found that the IPQ only added a small and non-substantial predictive value for poor recovery at 3 months in people with musculoskeletal pain. 10 For recovery expectations as a prognostic factor for LBP, a Cochrane review from 2019 concluded that having positive expectations towards recovery might be associated with a reduction in pain and disability, although the evidence was of low quality. 11 In general, there is evidence supporting a cross-sectional association between negative beliefs regarding LBP and higher levels of pain and disability.…”
Section: Introductionmentioning
confidence: 99%